Data and the Fourth Industrial Revolution. Issue 3 (26th May 2021) - Kenett, Ron; Coleman, Shirley
Abstract: Ron S. Kenett and Shirley Y. Coleman outline the roles played by data and statistics in "Industry 4.0", from monitoring manufacturing processes to the building of "digital twins"